Modelling tsunami bore-induced pressures on various seawall types - Mokhtar, Zaty Aktar (2019)
Catastrophic failures of many tsunami seawalls along the affected coasts during the 2011 Japan Tsunami has prompted extensive investigation into improving and revising design codes for tsunami defence structures. To date, researchers and coastal engineers are investigating to understand the failure mechanisms of seawall and to find solutions so that the structures merely remain intact in the extreme event such as tsunami. With this as the background, the main objective of this study was to experimentally investigate and quantify the tsunami bore-induced pressures exerted on various seawall types. In addition, the tsunami bore impact pressures on seawall models protected by a porous breakwater was also investigated. Four different seawall models; a solid vertical wall, a porous vertical seawall that consisted of a perforated front wall and a solid rear wall and two prevalent curved front seawalls, that were installed individually downstream in a 2D wave flume. Five impounding water depths (0.55, 0.60, 0.65, 0.70 and 0.75 m) were used to produce dam-break waves with various heights and velocities, which have been shown to be analogous to tsunami-induced bore characteristics as stated in theories. Time-history of bore pressures exerted on the seawall models were recorded. In additon, the flow depth-time histories were also recorded at various locations along the length of the flume. A high-speed video cameras together with a regular camera were used to monitor the bore-structure interaction. Experimental results revealed that there were significant differences between the measured pressures exerted on each seawall model. A high impulsive pressure was measured at the lowest-located pressure sensor of solid vertical wall model with 8 kPa in this study. It is found that the impulsive pressure recorded at other seawall models were less than that recorded at the solid vertical wall. It is also noted that the maximum pressure occurred at different times in one recorded time history of bore impacts for all seawall models. In addition, a partially submerged perforated wall with 30% porosity were installed upstream from the seawall models to investigate its efficiency as tsunami mitigation measures. Experimental results indicated that the maximum pressure exerted on the perforated seawall type can be reduced by approximately 20% to 50%. It was also revealed that the higher amount of pressure exerted on the upper section of the recurved seawall type can be reduced approximately 45% in the presence of the breakwater. The experimental measured data were also compared with those estimated from the current available formulations. The results and analysis presented in this study will be significant use to better understand the interaction between the tsunami bore and more complex seawall geometries. The findings from this study could also be used for validating any numerical models works as well as can be a guideline for future research in designing tsunami barrier structures.